A distant coilin homologue is required for the formation of cajal bodies in Arabidopsis. - Collier, S; Pendle, A; Boudonck, K; van Rij, T; Dolan, L; Shaw, P (2006)
Cajal bodies (CBs) are subnuclear bodies that are widespread in eukaryotes, being found in mammals, many other vertebrates and in all plant species so far examined. They are mobile structures, moving, fusing, and budding within the nucleus. Here we describe a screen for Arabidopsis mutants with altered CBs and describe mutants that have smaller Cajal bodies (ncb-2, ncb-3), lack them altogether (ncb-1), have increased numbers of CBs (pcb) or have flattened CBs (ccb). We have identified the gene affected in the ncb mutants as a distant homolog of the vertebrate gene that encodes coilin (At1g13030) and have termed the resulting protein Atcoilin. A T-DNA insertional mutant in this gene (ncb-4) also lacks Cajal bodies. Overexpression of Atcoilin cDNA in ncb-1 restores Cajal bodies, which recruit U2B'' as in the wild type, but which are, however, much larger than in the wild type. Thus we have shown that At1g13030 is required for Cajal body formation in Arabidopsis, and we hypothesize that the level of its expression is correlated with Cajal body size. The Atcoilin gene is unaffected in pcb and ccb, suggesting that other genes can also affect CBs.